Multibeam bathymetry raw data (Kongsberg EM712 entire dataset) of RV HEINCKE during cruise HE659 - Hoffmann, Jasper; Breyer, Gavin; Sander, Lasse; Sebastian, Hara; Rohde, Sven (PANGAEA, 2025)
Raw multibeam bathymetry data from the Kongsberg EM712 was acquired during the RV Heincke cruise HE659 in the German Bight in April 2025. The data was generally acquired during calm seas in water depths between 20 and 50 m. Primarily three different regions were surveyed (Borkumer Reef Ground, Sylt Outer Reef, and Helgoland). Generally the data is comprehensive and overlapping swaths creating a continuous bathymetry were archived. In some areas the data was acquired complementary to sidescan sonar surveys and individual tracks do not overlap. Data are unprocessed and therefore may contain some incorrect depth measurements (artifacts) without further processing. No tide variations are applied. Sound velocity profiles were acquired regularly. Overall, it appears that the data quality is rather good. The gridded data showed relatively few obstacles.
Keywords: Backscatter; Bathymetry; Kongsberg EM712; Multibeam Echosounder